Nanoenvelopes: Wrapping a Single‐Walled Carbon Nanotube with Graphene using an Atomic Force Microscope. Issue 45 (9th October 2018) - Hu, Xiao; Wei, Hang; Liu, Jia; Zhang, Jian; Chi, Xiannian; Jiang, Peng; Sun, Lianfeng
Abstract: Engineering the morphology and structure of low‐dimensional carbon nanomaterials is important to study their mechanical and electrical properties and even superconductivity. Herein, first the techniques that are used to engineer carbon nanotubes, including manipulation, morphology modification, and fabrication of complex nanostructures, are reviewed. This is followed by a summary of the methods applied to fabricate graphene nanostructures, such as heterostructures and nanoenvelopes of graphene. Lastly, an insight into the applications of low‐dimensional‐carbon‐based electronics is given, such as carbon nanotube (CNT) transistors, graphene‐based nanoenvelopes, and graphene‐contacted CNT field‐effect transistors (FETs), which are promising components in future electronics. Abstract : Engineering low‐dimensional carbon nanomaterials is important to study their novel properties. The techniques used to engineer carbon nanotube (CNT)‐based and graphene‐based nanostructures are reviewed, and recent progress regarding their applications, such as graphene‐contacted CNT devices is then introduced.